Quality Analysis Of Hots-Based Multiple Choice Questions On Government Accounting Elements Phase F Using Anates Software - Indrasari, Gupita Fayi; Fadhilah, Eva Nur; Inayah, Zanuba; Anandra, Shelayati Milani; Adila, Adila; Fatrotana, Aulia; Hafifa, Dwi Putri; Hakim, Luqman; Pratiwi, Vivi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study was conducted with the primary objective of evaluating the quality of Higher Order Thinking Skills (HOTS) multiple-choice questions developed for the Government/Institutional Accounting material for students in Phase F. The Anates application was used as the main tool in the analysis process. This quality evaluation was carried out to determine the extent to which the test items are feasible and effective as assessment instruments. The key quality indicators analyzed include validity, reliability, difficulty level, discrimination power, and distractor effectiveness.The research employed a quantitative approach using documentation methods and a survey design. The study will be conducted in a selected Vocational High School (SMK), involving Accounting Phase F students as participants. Data were collected through a set of 54 multiple-choice questions focusing on elements of Government/Institutional Accounting.The findings of this analysis are expected to provide valuable insights for the continuous improvement of test item quality and the learning outcome evaluation process in accounting education. This research is also expected to assist educators in developing assessment instruments that are more valid, reliable, and aligned with learning needs that require higher-order thinking skills.